Faktor-Faktor Yang Mempengaruhi Keberhasilan Penerapan Akuntansi Berbasis Akrual Pemerintahan Kabupaten Serdang Bedagai - Rizky Fauzy (Universitas Islam Negeri Sumatera Utara Medan, 2022)
This study aims to determine the factors that influence the success of the application of accrual-based accounting in the Serdang Bedagai Regency Government. This study uses a quantitative descriptive approach, aiming to determine the relationship between two or more variables. This study uses the entire population to be used as research samples, namely as many as 40 employees. The analysis technique used is multiple regression analysis. Based on the results of the partial test, it is known that the variables of Human Resources (X1), Motivation (X2) and Commitment (X3) have an influence on the Successful Implementation of Accrual-Based Accounting (Y). Based on the simultaneous test, the calculated f value is 11,056 with a sig level of 0.000, therefore the sig value is 0.000 > 0.05 and the F value is 11.056 > F table 2.87, this shows that Ho is rejected. Based on the coefficient of determination test, the value of R square (R2) or the square of R shows the determinant coefficient is 0.480, meaning that the percentage contributed by the Human Resources (X1), Motivation (X2) and Commitment (X3) variables affect the Accrual-Based Accounting Application (Y) of 48%.